HUBUNGAN OBESITAS DENGAN FAAL PARU PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - ., Satriyani; Pandelaki, Karel; Wongkar, M. C. P. (Universitas Sam Ratulangi, 2015)
Abstract: Obesity is a multifactor disease as the result of excessive accumulation of fat tissues that affect the reduction of respiratory compliance. Change of respiratory function by obesity affect lungs function, i.e. Forced Vital Capacity (FVC) and Forced Expiratory Volume in First Second (FEV1). The purpose of this research is to find out the correlation between Body Mass Index (BMI) and FVC and FEV1. This is a descriptive-analytic research with cross sectional method. Objects of the research were chosen with consecutive sampling technique. Subjects were 32 of Faculty of Medicine students, Sam Ratulangi University. FVC and FEV1 were measured using spirometry. The correlation between BMI and FVC and FEV1 were tested using Pearson correlation test. FVC mean value at grade I obesity is 116,92% pred. FVC mean value at grade II obesity is 98,47% pred. FVC mean value at grade II obesity is lower than grade I obesity. FEV1 mean value at grade I obesity is 118,23% pred. FEV1 mean value at grade II obesity is 107,16% pred. FEV1 mean value at grade II obesity is lower than grade I obesity. There is an insignificant negative correlation between FVC (r = -0,343; p = 0,054) and FEV1 (r = -0,297; p= 0,099). Conclusion: Increase in BMI can lower the lungs function, i.e. FVC and FEV1.Keywords: FVC, FEV1, obesityAbstrak: Obesitas merupakan suatu penyakit multifaktorial, yang terjadi akibat akumulasi jaringan lemak berlebihan, sehingga menurunkan compliance sistem pernafasan. Perubahan fungsi pernafasan akibat obesitas mempengaruhi nilai fungsi paru diantaranya Kapasitas Vitas Paksa(KVP) dan Volume Ekspirasi Paksa Detik Pertama(VEP1). Penelitian ini bertujuan untuk mengetahui hubungan Indeks Massa Tubuh dengan KVP dan VEP1. Penelitian ini bersifat deskriptif analitik dengan pendekatan cross sectional. Teknik pengambilan sampel yang digunakan yaitu consecutive sampling. Subyek penelitian adalah mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi dengan jumlah 32 subyek. KVP dan VEP1 diukur dengan menggunakan spirometer. Nilai mean KVP pada obese I ialah 116,92% pred, KVP obese II ialah 98,47% pred. Nilai mean KVP obese II 18,45% lebih rendah daripada obese I. Nilai mean VEP1 pada obese I ialah 118,23% pred, VEP1 obese II ialah 107,16% pred. Nilai mean VEP1 obese II 11,07% lebih rendah daripada obese I. Hubungan IMT dengan KVP dan VEP1 diuji dengan menggunakan uji korelasi pearson. Terdapat hubungan negatif non signifikan antara IMT dengan KVP (r = -0,343; p = 0,054) dan VEP1 (r = -0,297; p= 0,099). Simpulan: Peningkatan Indeks Massa Tubuh dapat menurunkan nilai fungsi paru diantaranya KVP dan VEP1.Kata Kunci: KVP, VEP1, obesitas